Postpartum hemorrhage and postpartum depressive symptoms: A retrospective cohort study. Issue 3 (15th February 2022) - Wang, Kewei; Qiu, Jun; Meng, Liping; Lai, Xin; Yao, Zhenzhen; Peng, Songxu
Abstract: Background: Many psychological and obstetrical factors contribute to the development of postpartum depression. However, little is known about how postpartum hemorrhage (PPH) influences postpartum depressive symptoms. This study explored the relationship between PPH and postpartum depressive symptoms in the Chinese population. Methods: A retrospective cohort study was conducted at the Baoan Maternal and Child Health Hospital in Shenzhen, China, from January 2016 to June 2020. The Edinburgh Postnatal Depression Scale was used to assess postpartum depressive symptoms. A multivariate logistic regression model was used to estimate the odds ratios (ORs) with 95% confidence intervals (95% CIs) between PPH and risk of postpartum depressive symptoms. Results: Of the 7734 respondents, 293 (3.8%) and 7441 were in the PPH and control groups, respectively. Puerperal women with PPH were more likely to screen positive for postpartum depressive symptoms than those without PPH (16.4% vs. 11.7%, p = .016). Adjusting for other covariates, women with PPH still had higher risk of postpartum depressive symptoms (OR = 1.68, 95% CI: 1.16–2.42). Stratification analyses revealed no interaction between PPH and maternal age, prepregnancy body mass index, mode of delivery, and fetal sex in developing depressive symptoms ( p for interaction > .05). Conclusions: PPH may increase the risk of postpartum depressive symptoms. Therefore, women with PPH should be actively screened for depressive symptoms in the immediate postpartum period.